Safety, pharmacokinetics, and biomarkers of F-652, a recombinant human interleukin-22 dimer, in healthy subjects - Tang, Kai-Yang; Lickliter, Jason; Huang, Zhi-Hua; Xian, Zong-Shu; Chen, Han-Yang; Huang, Cheng; Xiao, Chong; Wang, Yu-Peng; Tan, Ying; Xu, Lin-Feng; Huang, Yu-Liang; Yan, Xiao-Qiang (Cellular & molecular immunology, 2019)
F-652 is a recombinant fusion protein consisting of two human interleukin-22 (IL-22) molecules linked to an immunoglobulin constant region (IgG 2 -Fc). IL-22 plays critical roles in promoting tissue repair and suppressing bacterial infection. The safety, pharmacokinetics (PK), tolerability, and biomarkers of F-652 were evaluated following a single dose in healthy male volunteers in a randomized, double-blind, placebo-controlled study. Following single-dose subcutaneous (SC) injection of F-652 at 2.0 µg/kg into healthy subjects, six out of six subjects experienced delayed injection site reactions, which presented as erythematous and/or discoid eczematous lesions 10 to 17 days post-dosing. F-652 was then administered to the healthy subjects via an intravenous (IV) infusion at 2.0, 10, 30, and 45 µg/kg. No severe adverse event (SAE) was observed during the study. Among the IV-dosed cohorts, eye and skin treatment emergent adverse events (TEAEs) were observed in the 30 and 45 µg/kg cohorts. F-652 IV dosing resulted in linear increases in C max and AUC (0– t ) , and the T 1/2 ranged from 39.4 to 206 h in the cohorts. An IV injection of F-652 induced dose-dependent increases in serum marker serum amyloid A, C-reactive protein, and FIB, and decreased serum triglycerides. The serum levels of 36 common pro-inflammatory cytokines/chemokines were not altered by the treatment of F-652 at 45 μg/kg. In conclusion, IV administration of F-652 to healthy male volunteers is safe and well-tolerated and demonstrates favorable PK and pharmacodynamic properties. These results warrant further clinical development of F-652 to treat inflammatory diseases.